Increased Rates of Clostridium difficile Infection and Poor Outcomes in Patients with IBD with Cytomegalovirus. Issue 11 (November 2016) - McCurdy, Jeffrey D.; Enders, Felicity T.; Khanna, Sahil; Bruining, David H.; Jones, Andrea; Killian, Jill M.; Tariq, Raseen; Smyrk, Thomas C.; Loftus, Edward V.
Abstract : Background: Clostridium difficile infection (CDI) and Cytomegalovirus (CMV) reactivation are associated with disease exacerbations and poor outcomes in inflammatory bowel disease (IBD). Therefore, we assessed the association between these organisms in patients with IBD and the impact on colectomy. Methods: A retrospective case–control study was conducted to assess CDI prevalence in patients with IBD with a tissue diagnosis of CMV compared with matched IBD controls without CMV from 2005 to 2011. We also assessed the impact of coinfection on colectomy risk for patients coinfected with CMV and CDI compared with IBD patients with CMV alone (CMV controls) or matched IBD patients with CDI alone (CDI controls). Colectomy-free survival was assessed using Kaplan–Meier methods, and statistical significance was determined using Log-rank analysis for unmatched comparisons and by generalized estimating equations in Cox regression for matched comparisons. Results: CDI was more common in IBD patients with CMV (n = 12/68; 17.6%) than in matched IBD controls (n = 12/144; 8.25%) ( P = 0.046). A nonsignificant increase in high-grade disease (5 or more CMV inclusions by immunohistochemistry) was detected in coinfected patients compared with CMV controls ( P = 0.15). Colectomy-free survival at 1 year was 30% (95% confidence interval, 12.0–74.7) for coinfected patients and was significantly less compared with 71.5% (95% confidence interval, 58.0–88.2) of CDI controls ( P < 0.001) and was numerically less than 57.1% (95% confidence interval, 44.1–74.0) of CMV controls ( P = 0.095). Conclusions: CDI occurs more frequently in IBD patients with CMV reactivation and is associated with poor outcomes. Patients with IBD with CMV should be tested for CDI and managed aggressively. Abstract : Article first published online 12 October 2016.